Species richness from cropland to forest in Ghunsa valley, eastern Himalaya - Rajesh Tamang, Rajesh Tamang; Sanjeev K. Rai, Sanjeev K. Rai; Christoph Scheidegger, Christoph Scheidegger; Krishna K. Shrestha, Krishna K. Shrestha (International Journal of Indigenous Herbs and Drugs, 2018)
Objective: Species richness is the number of total species present in an ecological community which is widely used to measure biodiversity. The main aim of this study was to study variation in species richness along land use types, from cropland to forest.Methods: This study was carried out in Ghunsa valley, Kanchenjungha Conservation Area of Eastern Himalaya during 2012. Four land use types, namely cropland, meadow, exploited forest and natural forest were selected at each of five elevational bands starting from 2,200 m above sea level at Sekathum to 3,800 m asl at Rambuk kharka, Taplejung. A total of 70 transects, having 25 m × 2.5 m size, were laid and the vascular plant species found within each transect were recorded twice.Results: Altogether 360 species of vascular plants belonging to 257 genera and 95 families have been documented. Among them, 25 species belongs to pteridophytes, 7 species of gymnosperms and 328 species of angiosperms. One-way ANOVA showed the total species richness (including all groups) was significantly different (F3, 66= 7.494, p=0.000) in different land use types.Conclusion: Species richness was significantly different in different land use types. Species richness was found highest in exploited forest.